A Brief Discussion of Satre Existentialism: Exploring Sartre's Existential Phenomenology (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The philosophical career of Jean Paul Sartre (1905-1980) focuses, in its first phase, upon the construction of a philosophy of existence known as existentialism. Sartre's early works are characterized by a development of classic phenomenology, but his reflection diverges from Husserl’s on methodology, the conception of the self, and an interest in ethics. These points of divergence are the cornerstones of Sartre’s existential phenomenology, whose purpose is to understand human existence rather than the world as such. Adopting and adapting the methods of phenomenology, Sartre sets out to develop an ontological account of what it is to be human. The main features of this ontology are the groundlessness and radical freedom which characterize the human condition. These are contrasted with the unproblematic being of the world of things. Sartre’s substantial literary output adds dramatic expression to the always unstable co-existence of facts and freedom in an indifferent world.